The notion of reconciliation as part of the emerging coloured identity - Hendricks, Basil John (Department of Religious Studies, 2026)
The theology and practice of reconciliation emerged as a major issue of contention during the years of struggle for liberation in South Africa. While this notion is central to the Christian message of salvation and an obligation for all Christian believers, Christians differed among themselves depending upon their respective perceptions of the political struggle which ensued. White theologians urged the oppressed to join them in striving for unity and reconciliation, black and coloured Christians, however, were unanimous in their rejection of cheap reconciliation without justice. Since this country's first democratic elections in April 1994, South Africa has had to face many new challenges to the democratic process. One of these has been the new assertiveness of coloured people in the Western Cape where the coloured population are in the majority. Lately coloured people have expressed that they are unable to feel the blessings of reconciliation since they do not experience themselves as equally part of South Africa yet. Coloured people on the Cape Flats form the biggest section of the Catholic population in the Western Cape. The church which exists within history as a reconciled and reconciling community and as a sign for the 2 community around it, must have something to say to this! This paper attempts to persuade the regional Catholic hierarchy to permit its coloured countenance to be seen and for it to provide coloured people with the space to tell their story and to place it on the national agenda. This identification of the church with the aspirations of coloured people will involve the church itself in giving hope to those who dispair of the future and point to mutual respect and tolerance as the fruits of reconciliation. Part One of this dissertation is made up of three chapters. Chapters Two explores the theoretical underpinning of the notion of reconciliation by exploring biblical roots and the theological debate around reconciliation. Chapter Three deals with a critique of reconciliation in South Africa. Here I examine critique of the Kairos theologians and other prophetic theological voices in South Africa. Chapter Four deals with the South African Catholic Bishops Conference and other Catholic voices on the subject of reconciliation. Part Two of this dissertation is made up of four chapters. Chapter Five explores the history and development of the coloured community and of the effect of National Party racial policy on coloured people. Chapter Six examines racial segregation as a violation of human rights. Chapter Seven deals with the methodology involved designing a research survey 3 of coloured parishioners of Catholic communities on the Cape Flats. Chapter Eight concludes this section by presenting the research findings and discussions. Part Three of the dissertation I revisit my hypothesis that a disparity exists between the theological understanding of the hierarchical church and the cultural understanding of the notion of reconciliation of the coloured people. Part Three also consists of an evaluation of the research survey as well as recommendations for the church's mission in the Western Cape. Finally, it must be said that this is by far not an exhaustive study on the doctrine of reconciliation, but only to indicate its various meanings and its importance within religion and especially in Catholic theology and practice. Secondly, I am not trying to understand the whole question of coloured identity but to ascertain how this relates to Catholic church parishioners on the Cape Flats.